Five-year longitudinal surveillance reveals the continual circulation of both alpha- and beta-coronaviruses in Plateau and Gansu pikas (Ochotona spp.) at Qinghai Lake, China1 - Lin Xu; Meiqing Song; Xianzhi Tian; Ju Sun; Yanjun Wang; Mengyu Bie; Yuhai Bi; Edward C. Holmes; Yi Guan; Jianjun Chen; Juan Li; Weifeng Shi (Emerging Microbes and Infections)
The discovery of alphacoronaviruses and betacoronaviruses in plateau pikas (Ochotona curzoniae) expanded the host range of mammalian coronavirus (CoV) to a new order – Lagomorpha. However, the diversity and evolutionary relationships of CoVs in these plateau-region-specific animal population remains uncertain. We conducted a five-year longitudinal surveillance of CoVs harboured by pikas around Qinghai Lake, China. CoVs were identified in 33 of 236 plateau pikas and 2 of 6 Gansu pikas (Ochotona cansus), with a total positivity rate of 14.5%, and exhibiting a wide spatiotemporal distribution across seven sampling sites and six time points. Through meta-transcriptomic sequencing and RT–PCR, we recovered 16 near-complete viral genome sequences. Phylogenetic analyses classified the viruses as variants of either pika alphacoronaviruses or betacoronaviruses endemic to plateau pikas from the Qinghai-Tibet Plateau region. Of particular note, the pika-associated betacoronaviruses may represent a novel subgenus within the genus Betacoronavirus. Tissue tropism, evaluated using quantitative real-time PCR, revealed the presence of CoV in the rectal and/or lung tissues, with the highest viral loads at 103.55 or 102.80 RNA copies/μL. Surface plasmon resonance (SPR) assays indicated that the newly identified betacoronavirus did not bind to human or pika Angiotensin-converting enzyme 2 (ACE2) or Dipeptidyl peptidase 4 (DPP4). The findings highlight the ongoing circulation and broadening host spectrum of CoVs among pikas, emphasizing the necessity for further investigation to evaluate their potential public health risks.